2020
DOI: 10.3390/pharmaceutics12080731
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lipid Nanoparticles for Duodenum Targeted Oral Delivery of Tilmicosin

Abstract: Developing a targeted oral delivery system to improve the efficacy of veterinary antibiotics and reduce their consumption and environmental risks is urgent. To achieve the duodenum-targeted release of tilmicosin, the enteric granule containing tilmicosin-loaded solid lipid nanoparticles (TIL-SLNs) was prepared based on its absorption site and transport characteristics. The in vitro release, release mechanisms, stability, palatability, and pharmacokinetics of the optimum enteric granules were studied. The intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
(62 reference statements)
0
18
0
Order By: Relevance
“… Chitosan and Eudragit L-100 Insulin Oral insulin delivery system 130 43. Acrylic acid and methacrylic Rifampicin Sustained release and mucoadhesive delivery 131 44. Poloxamer 188, polyvinyl alcohol, and polyacryl resin II Tilmicosin Prevent gastrointestinal degradation 132 …”
Section: Enteric-coated Nanoparticle Formulations For Non-colorectal mentioning
confidence: 99%
“… Chitosan and Eudragit L-100 Insulin Oral insulin delivery system 130 43. Acrylic acid and methacrylic Rifampicin Sustained release and mucoadhesive delivery 131 44. Poloxamer 188, polyvinyl alcohol, and polyacryl resin II Tilmicosin Prevent gastrointestinal degradation 132 …”
Section: Enteric-coated Nanoparticle Formulations For Non-colorectal mentioning
confidence: 99%
“… 20 23 Zhou et al prepared TIM-loaded nanoparticles by hot melting with the ultrasonic emulsification method. 24 In addition, TIM-loaded lipid nanocarriers prepared through the high shear method display excellent storage and gastrointestinal stability and consequently enhanced oral absorption in broilers. 3 , 4 Zhou et al found that TIM-loaded in alginate-chitosan nanogels shows stronger sustained drug release compared with the injection of pure TIM.…”
Section: Introductionmentioning
confidence: 99%
“…This improved the in vivo anti-inflammatory efficacy of the formulation to rats with indomethacin-induced intestinal lesions, significantly reducing the ulcer index and the histological intestinal damage [ 212 ]. The ability of Tween 80 (polysorbate) to inhibit Pgp has also shown a promising role in the bioavailability enhancement of Pgp substrates [ 149 , 156 , 213 ]. In this line, Goo et al observed 4.1-fold permeation enhancement of valsartan, a Pgp substrate, through rat jejunum by its encapsulation in SNEDDS stabilized by Tween 80, as well as a 470% increase in its oral bioavailability in rats.…”
Section: Inhibition Of P-glycoproteinmentioning
confidence: 99%
“…Similarly, Zhou et al have recently exploited the potential of polysorbate-80 to inhibit drug efflux. These authors reported higher intestinal permeability of tilmicosin-loaded solid lipid nanoparticles when polysorbate-80 was added as Pgp inhibitor [ 213 ].…”
Section: Inhibition Of P-glycoproteinmentioning
confidence: 99%